2021
DOI: 10.1038/s41467-021-23678-9
|View full text |Cite
|
Sign up to set email alerts
|

Lateral advection supports nitrogen export in the oligotrophic open-ocean Gulf of Mexico

Abstract: In contrast to its productive coastal margins, the open-ocean Gulf of Mexico (GoM) is notable for highly stratified surface waters with extremely low nutrient and chlorophyll concentrations. Field campaigns in 2017 and 2018 identified low rates of turbulent mixing, which combined with oligotrophic nutrient conditions, give very low estimates for diffusive flux of nitrate into the euphotic zone (< 1 µmol N m−2 d−1). Estimates of local N2-fixation are similarly low. In comparison, measured export rates of sin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 49 publications
3
25
4
Order By: Relevance
“…Nitrate vs. fixed N supporting upper water column production in the deep waters of the GM While we do not discount subsurface nitrate inputs to the euphotic layer of the deep water region of the GM, zooplankton d 15 N values in our study suggest that nitrate cannot be the sole N source supporting primary and secondary production, contrary to what has been suggested by Knapp et al (2021) and Kelly et al (2021) for the northeastern gulf in the region of influence of the Loop Current. Knapp et al (2021) used sediment traps drifting below the euphotic layer in the north-central GM for 2-4 days during late spring to sample sinking particles, and measured their isotopic composition as well as that of subsurface nitrate. They used a box model approach and an d 15 N budget to evaluate the relative importance of N 2 fixation and subsurface NO 3 to export production.…”
Section: Potential Sources Of Light Din Within the Gmcontrasting
confidence: 99%
See 2 more Smart Citations
“…Nitrate vs. fixed N supporting upper water column production in the deep waters of the GM While we do not discount subsurface nitrate inputs to the euphotic layer of the deep water region of the GM, zooplankton d 15 N values in our study suggest that nitrate cannot be the sole N source supporting primary and secondary production, contrary to what has been suggested by Knapp et al (2021) and Kelly et al (2021) for the northeastern gulf in the region of influence of the Loop Current. Knapp et al (2021) used sediment traps drifting below the euphotic layer in the north-central GM for 2-4 days during late spring to sample sinking particles, and measured their isotopic composition as well as that of subsurface nitrate. They used a box model approach and an d 15 N budget to evaluate the relative importance of N 2 fixation and subsurface NO 3 to export production.…”
Section: Potential Sources Of Light Din Within the Gmcontrasting
confidence: 99%
“…Specifically, low d 15 N values of zooplankton (1.8‰ to 4‰) have been associated with high N 2 fixation rates measured in the GM during the summer (Holl et al, 2007), and Dorado et al (2012) reported low d 15 N values of zooplankton in the northern oceanic GM (2.8 ± 1.4‰) suggesting that N 2 fixation by Trichodesmium is an important N source in the LC and in LCE. In contrast, Knapp et al (2021) and Kelly et al (2021), based on indirect estimates, reported low N 2 fixation rates in the GM as a whole, suggesting that N 2 fixation is too small to be considered as a relevant N source; these authors also suggested that the low d 15 N values of POM were due to remineralization of primary producers supported by subsurface nitrate (Knapp et al, 2021;Kelly et al, 2021). On the other hand, cyclonic eddies with divergent conditions at their core lead to a shallower nitracline and pumping of subsurface NO 3 to the euphotic zone (Lee-Sańchez et al, 2022), while transport of NO 3 toward the surface can also occur due to a deepening of the mixed layer in winter (Müller-Karger et al, 2015;Damien et al, 2018).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…4c) could not reveal the increased mid-depth nitrate supply. Alternatively, such high NPP signal at mid-depth could also be a result of the lateral transport of organic matter (Kelly et al 2021).…”
Section: Seasonal Variations Of Surface and Depth-integrated Nppmentioning
confidence: 99%
“…Without the Southern Ocean nutrient source, the sum of the vertical processes that transport nutrients upwards across the pycnocline in the mid-and low-latitude ocean would be insufficient to maintain the biological productivity (Sarmiento et al, 2004). The horizontal transport of nitrate has been proved extremely important for productivity in subtropical circulation oligotrophic systems (Kelly et al, 2021;Letscher et al, 2016;Williams & Follows, 1998). It is foreseeable that the abundant nitrate in the upper seawater of the Antarctic Circumpolar Current (ACC) can be transported to the subtropical oligotrophic basin, according to the northward Ekman transport driven by westerly wind (Manabe et al, 1990).…”
mentioning
confidence: 99%